The mediating role of learning engagement in the relationship between master's students' learning motivation and scientific research and innovation capability - Hu, Ke; Tang, Dongmei; He, Huan (Frontiers in Education, 2025)
IntroductionParticipating in scientific research is a high-impact educational activity for master's students, and cultivating their scientific research innovation capabilities is a key goal of postgraduate education. While China boasts a large scale of higher education, apart from a small number of research-oriented universities, the majority of higher education institutions are local colleges and universities. Previous studies have mostly focused on the education of master's students in research universities, with insufficient attention paid to the cultivation of research innovation capabilities among master's students in local institutions. Existing research has indicated that learning motivation has a positive impact on learning engagement, and that learning engagement plays an active role in scientific research innovation capabilities. However, few studies have systematically examined the mediating function of learning engagement in this association.MethodsThis study employed a questionnaire survey method, collecting data from 3,301 master's students across eight universities in Fujian Province, with a final sample size of 3,050 valid responses. The data were analyzed using SPSS software through reliability and validity tests, descriptive statistics, and linear regression to explore the relationships among master's students' learning motivation, learning engagement, and scientific research and innovation capability.ResultsMaster's students in local colleges and universities demonstrate a relatively low level of scientific research innovation capability. Moreover, factors such as academic year, gender, and family background exert heterogeneous impacts on their scientific research innovation capability. Both intrinsic and extrinsic learning motivation positively predict scientific research innovation capability, with intrinsic learning motivation exerting a stronger effect. Specifically, the direct effect of intrinsic learning motivation on scientific research innovation capability outweighs its mediating effect, whereas the mediating effect of extrinsic learning motivation on scientific research innovation capability is more significant than its direct effect. Furthermore, different types of learning engagement exhibit heterogeneous influence mechanisms in the relationship between graduate students' learning motivation and scientific research innovation capability.DiscussionPostgraduate students' learning motivation positively predicts their scientific research innovation capability, and learning engagement exerts a significant impact on scientific research innovation ability. Learning engagement plays a mediating role between learning motivation and scientific research innovation ability. It serves as a “bridge,” facilitating the transformation of extrinsic learning motivation into intrinsic learning motivation and contributing to the improvement of postgraduate students' scientific research innovation capability. Nevertheless, the samples in this study are all from local universities in Fujian Province, which limits the promotion and application of the research conclusions.